Расчетно-экспериментальное определение усредненного числа квантованных продольных электронных полуволн де Бройля в цилиндрическом проводнике с импульсным аксиальным током - Баранов, Михаил Иванович; Рудаков, Сергей Валерьевич (Національний технічний університет "Харківський політехнічний інститут", 2020)
Представлены результаты теоретических и экспериментальных исследований, связанных с определением усредненного числа n0m квантованных продольных электронных полуволн де Бройля в металлическом проводнике с импульсным аксиальным током проводимости большой плотности. Полученные результаты указывют на квантово-волновой характер протекания импульсного тока проводимости в этом проводнике, приводящий к возникновению в его структуре квантованной продольной периодической локализации дрейфующих свободных электронов на участках шириной Δz. Данные зоны локализации электронов отличаются повышенной температурой нагрева.

Purpose. Implementation of calculation-experimental determination of average number n0m of the quantized longitudinal electron de Broglie half waves of length λezm/2 in the metal cylindrical conductor with the pulsed axial current of high density. Methodology. Scientific bases of theoretical lectrophysics and quantum physics, theoretical bases of the electrical engineering, electrophysics bases of technique of high-voltage and high pulsed currents. Results. The results of calculation-experimental estimations of average number n0m of the quantized longitudinal electron de Broglie half waves in the round continuous zincked steel wire of radius 0.8mm and of length 320 mm with aperiodic pulsed axial current i0(t) of temporal shape 9 ms/160 ms of high density (at its amplitude of δ0m=0.37 kA/mm2). It is shown that in examined case the numeral value of the average quantized number from data of calculation and experiment makes n0m=9, and test average length of quantized longitudinal electron de Broglie half waves in the indicated steel wire appears approximately equal to λezm/2≈34 mm. Electrophysical results are confirmed during the high current high temperature experiment conducted by a powerful high-voltage equipment calculation information on the choice of average value of quantized number n0m for longitudinal «hot» areas of the width Δz of the wire, different anomalous enhanceable concentration of drifting lone electrons and accordingly temperature of Joule heating. Originality. On the basis of the known conformities to the law of atomic and quantum physics new quantum-mechanical calculation correlation is obtained for determination in a metallic conductor with axial current of conductivity i0(t) of different type (direct, alternating and pulsed) of average number n0m of the quantized longitudinal electron de Broglie half waves and accordingly longitudinal «hot» areas of the width Δz of periodic localization along the conductor of drifting lone electrons. Practical value. Obtained results allow to make an evaluation prognosis on finding of possible places of longitudinal periodic localization of drifting lone electrons on narrow areas of the width Δz of current-carrying parts of power wires and cables of objects of electrical power energy, production and dwellings apartments, showing up most strongly (expressed) in malfunctions of operation of cable-conductor products with the currents of shortcircuit and high current density.
Calculation-experimental determination of the average number of quantized longitudinal electron de Broglie half waves in a cylindrical conductor with pulsed axial current
Keywords: полуволны де Бройля; усредненные числа; высоковольтные генераторы; импульсы тока; кабельно-проводниковая продукция; квантовые продольные полуволны; электроны; сублимация; продольные участки; высоковольтное оборудование; оцинкованные стальные проводы; metal conductor; pulsed current; longitudinal electron; de Broglie half waves